Implementation of Learning Through Research Internships for Social Science Education Students in Micro Enterprises at the Al-Fatimah Bojonegoro Pondok Pesantren - Prasetya, Sukma Perdana; Suryanti, Jun; Segara, Nuansa Bayu; Prastiyono, Hendri; Marzuqi, Muhammad Ilyas (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
The Merdeka Belajar Kampus Merdeka Program (MBKM) is one of the flagship programs of the Ministry of Education and Culture, which aims to encourage students to master various knowledge that is useful for entering the world of work. One form of learning activities offered is apprenticeship/practice. Internship aims to provide opportunities to apply theories that have been learned in lectures, as well as the application of general and specific skills in the world of work. Through the Kedaireka Matching Fund (MF) 2023 program, the Social Science Education study program, Unesa partnered with Micro Enterprises at the Al-Fatimah Bojonegoro, holding research internships. Research internships are attended by ten students for one semester. Data collection techniques used interviews with all research subjects, including documentation in the form of internship program manuals and student internship reports. Internship activities at Al-Fatimah Islamic Pondok Pesantren include three main activities, namely: workshops, observations, and entrepreneurial practices. During the internship, students make various household cleaning products such as detergent, dish soap, perfume and so on. Students also sell household cleaning products, whether marketed directly to consumers, trade fairs or marketing using online media. The results of the activity show that the apprenticeship program at Al-Fatimah Bojonegoro Pondok Pesantren Micro Enterprise provides hands-on learning experience for Social Sciences Education students to manage entrepreneurship starting from managing trademarks, optimizing production, optimizing marketing and managing cooperatives. The internship experience also adds soft skills, so that students are ready to compete and open up new business opportunities.